2007
DOI: 10.1021/cm0621601
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Response of an Organic−Inorganic Perovskite:  Methylammonium Lead Bromide

Abstract: The behavior of the organic-inorganic perovskite, methylammonium lead bromide, as a function of pressure was studied up to pressures slightly above 3 GPa at temperatures between ambient and ∼80 K using neutron diffraction. The sample transforms from Pm3 hm to Im3 h just below 1 GPa and amorphizes around 2.8 GPa without the cations undergoing long-range orientational ordering. The response of the orientationally ordered Pnma phase to pressure, which could not be accessed experimentally, was studied with density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
169
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(192 citation statements)
references
References 33 publications
23
169
0
Order By: Relevance
“…Fig. to I4/mcm at 236.3 K, to P4/mmm at 154.0 K, and to Pna21 at 148.8 K), 50 while only one phase transformation from Pm-3m to Im-3 under high pressure (below 1 GPa) was reported by Swainson et al 41 They also suggested an orthorhombic phase with space group Pnma under higher pressure by DFT calculations. With the increase of pressure, some sharp rings become weaker and new broad rings appear, indicating the onset of structural disorder and partial amorphization.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Fig. to I4/mcm at 236.3 K, to P4/mmm at 154.0 K, and to Pna21 at 148.8 K), 50 while only one phase transformation from Pm-3m to Im-3 under high pressure (below 1 GPa) was reported by Swainson et al 41 They also suggested an orthorhombic phase with space group Pnma under higher pressure by DFT calculations. With the increase of pressure, some sharp rings become weaker and new broad rings appear, indicating the onset of structural disorder and partial amorphization.…”
Section: Resultsmentioning
confidence: 84%
“…41 The asgrown orange microcrystals show good phase purity in cubic phase with space group Pm-3m (lattice constants of a = 8.4413(6) Å), and green emission under UV irradiation (As shown in Fig. 41 The asgrown orange microcrystals show good phase purity in cubic phase with space group Pm-3m (lattice constants of a = 8.4413(6) Å), and green emission under UV irradiation (As shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…61 The volume reduction under compression was attributed to the tilting of PbBr 6 octahedra. Suga and co-workers also gave the pressure-temperature phase relations of CH 3 NH 3 PbX 3 (X= Cl, Br, I) crystals in the range between 0.1 Pa and 200 MPa in detail.…”
Section: Crystal Structure Stability Of Perovskitementioning
confidence: 99%
“…I. P. Swainson et al studied the structural transition behavior of MAPbBr 3 as a function of pressure (slightly above 3 GPa) and temperature (RT ≈ 80 K). [ 110 ] They found that the energy gain for orientational ordering was low and the reduction of the unit cell volume was the main driving force for the transitions of the perovskite compounds under pressure. Evidently, the phase transition/symmetry variation caused by octahedra tilting signifi cantly infl uences the electronic and optical properties of the perovskites, and affects the photovoltaic performance of MPSCs.…”
Section: Thermal Effectmentioning
confidence: 99%